DEVELOPMENT OF ACCOUNTING MODULE WITH COMPETENCY BASED TRAINING (CBT) MODEL TO IMPROVE CLASS PARTICIPANTS IN BALAI LATIHAN KERJA KOTA KUPANG IN 2018 - Yuninda Anaci Lulan, Jacob Abolladaka (International Journal of Advanced Science and Technology, 2020)
The Competency Based Training Module at the Kupang Vocational Training Center in the journal entry processing unit competence. This learning module development research applied Dick, Carey and Carey modified into 9 stages: 1) learning objectives, 2) conducting instructional analysis, 3) analyzing student and context, 4) formulating particular objectives / for working, 5) developing the research instruments, 6) developing learning strategies, 7) designing and implementing the formative evaluation, 9) revising the teaching materials. The analysis of the data applied during the development of descriptive analysis, the analysis of the appropriateness module was done based on the criteria score, and the analysis of the training of competent participants was done through the t-test. The product of development is tested in a vocational training center through several stages, they are: review of media experts, subject matter experts, linguists, practitioners experts, small group testing and field trials for 32 participants of training.  The result is that the development of the accounting module with the Competency Based Training is effective for training the participants of the Vocational Training Center in Kupang . This is an increase in the competency score in the pre-test and post-test. The t-test is indicated that the mean of the pre-test (before) is 62.06 and the mean of post-test (after) is 79.25. There is an increase of 17, 19 points, with the significant value of (0,000) <0.05 and the tv value of 8.537> ttable 2,039.